Pleomorphic adenoma of the palate: a case report and review of the literature - Rahnama, Mansur; Orzędała-Koszel, Urszula; Czupkałło, Łukasz; Łobacz, Michał (Contemporary Oncology/Współczesna Onkologia, 2013)
Salivary gland tumors are rare and account for 2–3% of tumors occurring in the head and neck. Pleomorphic adenoma is a benign neoplasm which is commonly encountered in the parotid gland and other major salivary glands. At times they can also develop in minor salivary glands of the palate. The majority of minor salivary gland tumors are malignant. This case report describes a case of mixed tumor in a minor salivary gland of the hard palate.